2014
DOI: 10.1186/2045-8118-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Brain disposition of α-Synuclein: roles of brain barrier systems and implications for Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the accumulation of α-Synuclein (a-Syn) into Lewy body inclusions and the loss of dopaminergic neurons in the substantia nigra (SN). Accumulation of a-Syn can induce a progressive, cyclical pathology that results in the transmission of toxic, aggregated a-Syn species to healthy neurons, leading to further neurodegeneration such as occurs in PD. The blood–brain barrier (BBB) and blood-cerebrospinal fluid (CSF) barriers (BCSFB) are respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
(90 reference statements)
2
31
0
Order By: Relevance
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 82%
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 82%
“…Alpha-synuclein is expressed in the rat CP, primary culture of CP cells and an immortalized line of rat CP epithelial cells (Z310). This indicates that the CP can transport alpha-synuclein between the blood and CSF [256,257]. However, this transport mechanism is not fully understood and needs further examination.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…These transport properties, however, have yet to be thoroughly investigated at the BCSFB or BBB. For detailed discussions, please see a recent review by Bates and Zheng [19]. …”
Section: Introductionmentioning
confidence: 99%